German economy remaining robust in uncertain times - Claus Michelsen; Christian Breuer; Martin Bruns; Marius Clemens; Max Hanisch; Simon Junker; Thore Schlaak (DIW Weekly Report, 2018)
The German economy will keep on growing amid risks although growth will slow down somewhat. GDP will continue to grow noticeably at 1.8 percent this year, 1.7 percent next year, and 1.8 percent in 2020. Private household incomes in particular-and thus consumption as well-are boosting growth, as the labor markets are improving: the unemployment rate will fall from 5.2 percent this year to well below five percent in 2020 and lead to stronger wage increases. However, inflation will remain moderate at almost two percent.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook